2007
DOI: 10.1007/s11764-007-0029-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of cancer support groups among Latina breast cancer survivors

Abstract: More effort should be directed toward providing culturally and linguistically appropriate support services to breast cancer survivors, and increasing awareness of these services among oncologists, patients and family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 49 publications
0
45
1
Order By: Relevance
“…29 We did, however, anticipate that more women would identify as having joined a BC support group, with the percentage of women in our study who joined a support group being almost half that reported by others. 30,31 This may indicate that in more recent times, with the widespread use of the Internet, women feel that they have sufficient access to information without actively joining a BC support group.…”
Section: Discussionmentioning
confidence: 99%
“…29 We did, however, anticipate that more women would identify as having joined a BC support group, with the percentage of women in our study who joined a support group being almost half that reported by others. 30,31 This may indicate that in more recent times, with the widespread use of the Internet, women feel that they have sufficient access to information without actively joining a BC support group.…”
Section: Discussionmentioning
confidence: 99%
“…Due to population trends of increasing age and the advances in cancer screening, treatment, and quality of survivorship care, the number of older cancer survivors is expected to double over the next 50 years [2]. Although there are well-known disparities in breast cancer outcomes between Hispanic and nonHispanic white (NHW) women in the USA [3,4], more Hispanic women are surviving cancer because of these improvements in screening and access to recommended treatment [5,6]. Hispanic survivors are projected to account for an increasing proportion of the vastly growing breast cancer survivor population [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…These factors may also affect their attitudes and use of cancer support services. Transportation and childcare needs also can prevent Latinas from participating in group support programs (19). Furthermore, language differences may prevent physicians from engaging in a discussion of psychosocial needs and services with their Spanish-speaking patients.…”
Section: Introductionmentioning
confidence: 99%